Utilization Of Board Game Flofahunt Media To Train Students' Critical Thinking Skills In Grade V Science Material At SDN 216 Sondariah, Bandung City - Winda Nur Azizah; Dede Trie Kurniawan; Rendi Restiana Sukardi (Jurnal Ilmiah Mandala Education (JIME), 2025)
FloFaHunt is an educational game-based learning media designed to integrate biodiversity content—specifically Indonesian flora and fauna—with an active and enjoyable learning approach. This study employed a mixed methods approach using a concurrent embedded design, combining quantitative and qualitative data through critical thinking tests and student response questionnaires. By implementing the STAD-type cooperative learning model with the  FloFaHunt board game, the learning outcomes showed a significant improvement in students’ critical thinking skills, with the average n-gain score falling into the high category. Meanwhile, the qualitative data revealed that students responded positively to the learning process, particularly in terms of engagement, enthusiasm, and conceptual understanding. These findings indicate that the use of the FloFaHunt board game is effective in fostering critical thinking skills and active